Macradenia (Orchidaceae): a confirmed genus for Costa Rican Flora - Pupulin, Franco (2016)
The presence of the orchid Macradenia brassavolae Rchb.f. is confirmed in Costa Rica on the basis of two collections from the Caribbean drainage. The species is described and illustrated.